Control of emerging and re-emerging zoonotic and vector-borne diseases in countries of the Eastern Mediterranean Region - Chughtai, Abrar Ahmad; Kodama, Chiori; Joshi, Rohina; Tayyab, Muhammad; Paiman, Mohammad Akbar; Abubakar, Abdinasir (Frontiers in Tropical Diseases, 2023)
Despite improvement in detection and control of infectious diseases, many new pathogens are emerging and re-emerging from various parts of the world. Most of these emerging and re-emerging infections are of zoonotic origin, which highlights the importance of human-animal interface.Similarly, the rate of vector borne diseases has increased recently due to changes in human habitat and climate, deforestation, changes in food production practices and increased population movement.The risk spread of these zoonotic and vector borne diseases is higher in the Eastern Mediterranean Region (EMR) of the World Health Organization due to its topography and geopolitical situation, fragile health systems, complex humanitarian emergencies and other socioeconomic risk factors in some countries. Many countries of the region have reported outbreaks of zoonotic and vector borne diseases over the last few decades, and some of them have spread to other WHO regions as well.Avian influenza A (H5N1) and Middle East respiratory syndrome coronavirus (MERS-CoV) are among the greatest threats to global health security and both viruses are endemic in the EMR.Countries in the EMR have made significant progress towards the control of zoonotic and vector borne diseases in recent years and prevention, preparedness and response capacities have been improved. However, there are still many challenges in control of these diseases in the EMR, particularly in countries facing humanitarian emergencies. In this paper we will present the current situation of emerging and re-emerging infections in the EMR and will discuss progress, challenges, and way forward.